2003
DOI: 10.1046/j.1365-2958.2003.03657.x
|View full text |Cite
|
Sign up to set email alerts
|

PknB kinase activity is regulated by phosphorylation in two Thr residues and dephosphorylation by PstP, the cognate phospho‐Ser/Thr phosphatase, in Mycobacterium tuberculosis

Abstract: SummaryBacterial genomics revealed the widespread presence of eukaryotic-like protein kinases and phosphatases in prokaryotes, but little is known on their biochemical properties, regulation mechanisms and physiological roles. Here we focus on the catalytic domains of two trans -membrane enzymes, the Ser/ Thr protein kinase PknB and the protein phosphatase PstP from Mycobacterium tuberculosis . PstP was found to specifically dephosphorylate model phospho-Ser/Thr substrates in a Mn 2+ + + + -dependent manner. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
193
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(210 citation statements)
references
References 58 publications
15
193
2
Order By: Relevance
“…In addition to activation loop phosphorylation, sites in the intracellular juxtamembrane region, which has been hypothesized to have a regulatory function, were identified for PknA, PknB, and PknD (19,20). Some of these sites were previously shown to be phosphorylated in vitro (19)(20)(21). In contrast to the other protein kinases, we found that PknG is phosphorylated near its amino terminus, also consistent with previous in vitro results (8).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to activation loop phosphorylation, sites in the intracellular juxtamembrane region, which has been hypothesized to have a regulatory function, were identified for PknA, PknB, and PknD (19,20). Some of these sites were previously shown to be phosphorylated in vitro (19)(20)(21). In contrast to the other protein kinases, we found that PknG is phosphorylated near its amino terminus, also consistent with previous in vitro results (8).…”
Section: Resultssupporting
confidence: 90%
“…We found that four STPKs (PknA, PknB, PknD, and PknG) were phosphorylated in vivo. In addition to activation loop phosphorylation, sites in the intracellular juxtamembrane region, which has been hypothesized to have a regulatory function, were identified for PknA, PknB, and PknD (19,20). Some of these sites were previously shown to be phosphorylated in vitro (19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, potential phospho-threonine sites on PknH to which EmbR might bind had to be inferred from data of other Mtb Pkn kinases, whereby phospho-Thr sites 171 and 173 in the activation loop of PknB had been reported to play a critical role for both kinase activation (30) and substrate binding (12). Of these sites, Thr-171 (Thr-170 in PknH) is conserved in all but 2 of the 11 Mtb Ser͞Thr kinases.…”
Section: Resultsmentioning
confidence: 99%
“…We thus concluded that Thr-168 was a residue that was intermolecularly autophosphorylated. Self-activation of AfsK by phosphorylation of a single Thr residue in the activation loop is the same as for eukaryotic PKA [11,12], but a contrast with M. tuberculosis PknB [8] that self- A. AfsK, PkaG, and AfsL are from Streptomyces; Pkn kinases, from Mycobacterium; PrkC, from Bacillus; Pkn1 and Pkn4, from Myxococcus; and PKA, from Mus musculus. Highly conserved amino acids are shaded.…”
Section: Site-directed Mutagenesis Of Ser-71 Ser-128 Thr-168 and Thmentioning
confidence: 94%
“…All these kinases autophosphorylate on two or more threonine residues in the activation loop. The two phosphorylated threonines in PknB are both important for activation of its kinase activity [8,9]. On the other hand, phosphorylation of one threonine residue in the activation loop is important for mammalian cAMP-dependent protein kinase A (PKA) [11,12] and AMP-activated protein kinase (AMPK) [13].…”
mentioning
confidence: 99%